Symbolic Exchange and Brand Construction: Business Communication in Garut Leather’s Product Design - Handrini Ardiyanti; Mila Karmila; Salman Maulana; Ayu Larasati; Ummanah (Communicology: Jurnal Ilmu Komunikasi, 2025)
The Garut leather industry has demonstrated significant growth, driven by rising consumer demand for high-quality, locally produced goods. To sustain this development, Micro, Small, and Medium Enterprises (MSMEs) must strengthen product design strategies and creative communication approaches. This study explores how business communication - through symbolic exchange embedded in design elements such as functionality, aesthetics, and innovation -contributes to the construction of brand identity in Garut leather products. Employing a qualitative approach, the research integrates market observation, consumer feedback analysis, and in-depth interviews with local producers. NVivo software is used to code and analyze data, enabling systematic identification of key themes in consumer perception and symbolic design. Findings indicate that features such as RFID-blocking technology, improved compartmental organization, and eco-conscious materials are not only functional enhancements but also serve as communicative symbols of modernity, trust, and craftsmanship. These symbolic design innovations play a crucial role in shaping consumer-brand relationships and enhancing market competitiveness. The study concludes that symbolic value in product design functions as an effective form of business communication, enabling MSMEs to articulate cultural identity while addressing evolving consumer expectations. This strategy is essential for positioning Garut leather products in both domestic and global markets.